Antioxidant Stress and Anti-Inflammation of PPARα on Warm Hepatic Ischemia-Reperfusion Injury. (11th November 2012) - Gao, Zhixin; Li, Yuan-Hai
Abstract : Hepatic ischemia-reperfusion (IR) injury is a serious clinical problem. Minimizing the adverse effect of ischemia-reperfusion injury after liver surgery or trauma is an urgent need. It has been proved that besides the effect of regulating the lipid and lipoprotein metabolism, PPAR α also undertakes the task of organ protection. In this paper, related literature has been summarized and we come to the conclusion that administration of PPAR α agonists can strengthen the antioxidant and anti-inflammation defense system by the upregulation of the expression of antioxidant enzymes and inhibition of NF- κ B activity. This may provide a potential clinical treatment for hepatic ischemia-reperfusion injury.